Brand personality: Current insights and future research directions - Calderón Fajardo, Víctor; Molinillo-Jiménez, Sebastián; Anaya-Sánchez, Rafael; Ekinci, Yuksel (Elsevier, 2023)
The aim of this study is to improve the understanding of the scientific contributions made by brand personality (BP) research, to identify its predominant themes and to propose a relevant research agenda. An analysis was undertaken of the 1051 brand personality-related articles published over the period 1987–2022 that are indexed in the Scopus scientific database. A bibliometric approach was adopted to systematically analyse the publications, and a performance analysis and science mapping were undertaken. The results showed that the motor themes of BP research related to its conceptualisation, dimensions and measurement, its impact on consumer-brand relationships and application in tourism destination-focused studies. Emerging BP-focused themes are its applications in virtual reality, artificial intelligence, service robots, storytelling and tourism segments, such as luxury. This study contributes by providing a better understanding of the state-of-the-art research on BP, and by identifying future research directions
Keywords: Bibliometría; Relaciones con el cliente -- estudios; Brand personality; Literature review; Bibliometric analysis; Text mining; Science mapping; Co-word analysis